AGE-Monitoring and managing health and age at work - Ramos, S.; Carvalho, H. (International Interdisciplinary Conference Work, age, health and employment – evidence from longitudinal studies, 2016)
Background: Ageing of the population, particularly in the workforce, is perhaps the greatest current challenge to which European societies should respond. Despite the increasing attention to demographic trends, the study of the relationship between age and work has remained at a macro level with little impact on what happens inside the organizations. The complex relationship between age and work goes beyond the association between the exposure to risk factors and early aging. Only few studies attempt to encompass this complexity and try to put this discussion in a temporal dimension, considering the developments of health and work over lifetime. European studies, as ESTEV and VISAT, both in France, used a longitudinal design with repeated measures in order to monitor health issues taking into account job modifications and age evolution. From these experiences, other studies were performed in this field, with less extensive instruments, for example the SVP50 and EVREST. In Portugal we are now developing the first survey on health and age – AGE– based on the previous experiences and supported by the strong network between researchers from these groups. Method: The first AGE data collection started in 11/2015 and ended in 3/2016, in collaboration with the National Authority for Working Conditions, with a sample of 3000 workers from several sectors. It's planned to have further data collection within 5 years. Results: At this moment we are starting the data analysis. AGE dimensions focuses on working conditions (working time, schedules, demands/resources, perceived risks); health complaints (and their relation with work), in order to analyse the relationship between age, health and work; and questions about retirement expectations, in order to identify retirement predictors. Discussion/Conclusion: This study will contribute to developing conditions to raise the employment rate of older workers by an efficient monitoring of health and exposure to working conditions.